Electrocardiographic diagnosis of healed myocardial infarction in patients with left bundle branch block - Rungroj Krittayaphong (2018)
Healed myocardial infarction (MI) in patients with left bundle branch block (LBBB) is difficult to diagnose by electrocardiogram (ECG). This study was to determine accuracy of various ECG criteria for the diagnosis of MI in patients with LBBB. We studied patients with LBBB who were referred for cardiac magnetic resonance (CMR) for the assessment of cardiac function and myocardial viability by late gadolinium enhancement (LGE). ECG and CMR were performed on the same day. We determined accuracy of the following ECG criteria: 1) notching S in V3-V5, 2) notching R upstroke in lateral leads or rSR', 3) Q wave in lateral leads, 4) Q wave or inverted T wave in inferior leads, 5) R' or notched R wave in aVF, and 6) abnormal precordial R wave progression. We used LGE by CMR as the gold standard for the diagnosis of MI. There were 47 males (44.3%) and 59 females (55.7%) with an average age of 67 ± 13 years. Diagnosis of MI by LGE was made in 37 patients (36.7%). Sensitivity of ECG criteria ranged from 12.8 to 33.3% with specificity of 61.2 to 95.5% and accuracy of 50.9 to 68.9%. The highest sensitivity criteria were notching R wave upstroke in lateral leads or rSR' and Q wave or T wave inversion in inferior leads. The highest specificity was abnormal precordial R wave progression. The highest accuracy was Q wave or T wave inversion in inferior leads. Analysis by specific MI locations showed that the diagnostic yield increased for anterior and inferior wall MI. We concluded that ECG had a limited sensitivity and high specificity for the diagnosis of MI in patients with LBBB.